From Statistical to Geolinguistic Data: Mapping and Measuring Linguistic Diversity - Monica Barni (Fondazione Eni Enrico Mattei (FEEM), 2006)
The aim of this paper is describing a new methodology for mapping and measuring linguistic diversity in a territory. The three methods that have been created by the Centro di eccellenza della ricerca Osservatorio linguistico permanente dellitaliano diffuso fra stranieri e delle lingue immigrate in Italia at the Università per Stranieri di Siena are the following: the Toscane favelle model, a procedural application which passes from quantitative statistical data to a demolinguistic paradigm; - the Monterotondo-Mentana model. The surveys of quantitative and qualitative data are carried out using traditional tools (questionnaires, audio and video recordings) as well as advanced technologies; - the Esquilino model. Digital maps are created which present the distribution of the immigrant languages through the presence of signs in linguistic landscape. The final objective is putting together the data surveyed by the three methods in order to have a speaking territory, in which each point surveyed identifies the languages spoken and the various linguistic manifestations.
Keywords: I28; 330; Language Contact; Linguistic Diversity; Immigrant Languages; Geolinguistic Data; New Methodologies in Sociolinguistic Research